Is Green Management Applied to Manufacturing Companies in Sukabumi? - dewi herawati; Mariati Tirta Wiyata (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2022)
This study aims to analyze the application of green management to one of the manufacturing companies in Sukabumi City. This research uses a qualitative descriptive method, which is in the form of an analysis that describes the data that is the focus of this study, namely explaining how the application of green management to one of the manufacturing companies in Sukabumi City. In this study, the data collection techniques used were observation, interviews and documentation. Data analysis is carried out based on aspects regarding green management, namely related to the legal approach, market approach, stakeholder approach and activist approach. The results of this study found that the company that was the location of this study was quite good in implementing green management, besides that this company also carried out its business ethics by implementing Corporate Social Responsibility (CSR) programs.